A novel linear electromagnetic-drive oil-free refrigeration compressor using R134a - Liang, K; Stone, R; Dadd, M; Bailey, P (Elsevier, 2013)
A new type of oil-free moving magnet linear compressor with clearance seals and flexure springs has been designed for incorporation into a vapour compression refrigeration system with compact heat exchangers for applications such as electronics cooling. A linear compressor prototype was built with a maximum stroke of 14 mm and a piston diameter of 19 mm. An experimental apparatus was built to measure the compressor efficiencies and coefficient of performance (COP) of a refrigeration system with the linear compressor, using R134a. The resonant frequency for each operating condition was predicted using the discharge pressure, suction pressure and stroke. Refrigeration measurements were conducted for different strokes under each pressure ratio with a fixed condenser outlet temperature of 50 °C and evaporator temperature ranging from 6 °C to 27 °C. The results show that the COPs are around 3.0 for tests with a pressure ratio of 2.5 (evaporator temperature of 20 °C). © 2013 Elsevier Ltd and IIR. All rights reserved.